CELLULITIS IN THE ANTERIOR TIBIA AND POSTERIOR SINISTRA REGION: (PEER REVIEW) - Deri Ezra; Asrawati Sofyan; Tri Setyawati (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2022)
Cellulitis is an acute bacterial infection of the skin. Infection that occurs spreads to the dermis and sub cutis layer. This infection is usually preceded by injury or trauma with the most common causes are Streptococcus beta hemolyticus and Staphylococcus aureus. A 55-year-old male patient entered with complaints of injuries and swelling in his left leg that had been experienced since 2 weeks ago and was previously treated at Madani Hospital and given treatment by a doctor. The patient said that initially a painful lump appeared in the groin area, a few days later the redness appeared on the thigh and then spread to the calf. Physical examination revealed crusting at the side of the erythema squamous and macular in the anterior tibia et posterior sinistra.